Leveraging on the genomics and immunopathology of SARS-CoV-2 for vaccines development: prospects and challenges. Issue 3 (4th March 2021) - Abdullahi, Idris Nasir; Emeribe, Anthony Uchenna; Adekola, Hafeez Aderinsayo; Abubakar, Sharafudeen Dahiru; Dangana, Amos; Shuwa, Halima Ali; Nwoba, Sunday Theophilus; Mustapha, Jelili Olaide; Haruna, Muyideen Titilope; Olowookere, Kafayat Adepeju; Animasaun, Olawale Sunday; Ugwu, Charles Egede; et al.
ABSTRACT: The incidence and case-fatality rates (CFRs) of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, the etiological agent for Coronavirus Disease 2019 (COVID-19), have been rising unabated. Even though the entire world has been implementing infection prevention and control measures, the pandemic continues to spread. It has been widely accepted that preventive vaccination strategies are the public health measures for countering this pandemic. This study critically reviews the latest scientific advancement in genomics, replication pattern, pathogenesis, and immunopathology of SARS-CoV-2 infection and how these concepts could be used in the development of vaccines. We also offer a detailed discussion on the anticipated potency, efficacy, safety, and pharmaco-economic issues that are and will be associated with candidate COVID-19 vaccines.